The Tolerance Based on Rainer Forst in the Perspective of Islamic Religious Education - Wiranata, Rz. Ricky Satria; Maragustam, Maragustam; Sukiman, Sukiman (Tadris: Jurnal Keguruan dan Ilmu Tarbiyah, 2026)
Abdul-Jabbar, W. K., & Makki, Y. (2024). Integrating intercultural philosophy into the high school curriculum: Toward a deliberative pedagogy of tadabbur in diasporic Muslim education. Religions, 15(2), 189. https://doi.org/10.3390/rel15020189 Aderibigbe, S. A., Idriz, M., Alzouebi, K., AlOthman, H., Hamdi, W. B., & Companioni, A. A. (2023). Fostering tolerance and respect for diversity through the fundamentals of Islamic education. Religions, 14(2), 212. https://doi.org/10.3390/rel14020212 Afriyanto, D., & Anandari, A. A. (2024). Transformation of Islamic religious education in the context of multiculturalism at SMA Negeri 9 Yogyakarta through an inclusive approach. Jurnal Pendidikan Agama Islam, 21(1), 1–21. https://doi.org/10.14421/jpai.v21i1.7142 Agbaria, A. (2024). Education for religion: An Islamic perspective. Religions, 15(3), 309. https://doi.org/10.3390/rel15030309 Al Arood, M. A. S., Aljallad, M. Z., & Baioumy, N. (2020). The effectiveness of a cloud-based learning program in developing reflective thinking skills in Islamic education among students in UAE. International Journal of Education and Practice, 8(1), 158–173. https://doi.org/10.18488/journal.61.2020.81.158.173 Alhashmi, M., Bakali, N., & Baroud, R. (2020). Tolerance in UAE Islamic education textbooks. Religions, 11(8), 377. https://doi.org/10.3390/rel11080377 Banks, J. A. (2008). Diversity, group identity, and citizenship education in a global age. Educational Researcher, 37(3), 129–139. https://doi.org/10.3102/0013189X08317501 Bergamaschi, A., Blaya, C., Arcidiacono, F., & Steff, J. (2022). Blatant and subtle prejudice, and the role of teachers in conveying tolerance and respect for the other. Intercultural Education, 33(1), 17–34. https://doi.org/10.1080/14675986.2021.2017643 Brooks, C., & Weber, N. (2022). Liberalization, education, and rights and tolerance attitudes. Social Science Research, 101, 102620. https://doi.org/10.1016/j.ssresearch.2021.102620 Creswell, J. W., & Creswell, J. D. (2022). Research design: Qualitative, quantitative, and mixed methods approaches (6th ed.). SAGE Publications. Demirel Ucan, A., & Wright, A. (2019). Improving the pedagogy of Islamic religious education through an application of critical religious education, variation theory and the learning study model. British Journal of Religious Education, 41(2), 202–217. https://doi.org/10.1080/01416200.2018.1484695 Drerup, J. (2021). Education, epistemic virtues, and the power of toleration. Critical Review of International Social and Political Philosophy, 24(1), 108–131. https://doi.org/10.1080/13698230.2019.1616883 Fitriani, M. I. (2023). Islamic religious education and interreligious tolerance in a multi-religious country: Challenges, typological implications, and the proposed strategy. Ulumuna, 27(1), 416–449. https://doi.org/10.20414/ujis.v27i1.765 Forst, R. (2013). Toleration in conflict: Past and present (C. Porter, Trans.). Cambridge University Press. Forst, R. (2019). Toleration, power and reason: Continuing a dialogue with a political realist friend. Biblioteca Della Libertà, 54(230), 1–16. Fraenkel, J. R., Wallen, N. E., & Hyun, H. H. (2019). How to design and evaluate research in education (10th ed.). McGraw-Hill Education. Hakim, M. L., Qurbani, I. D., & Wahid, A. (2023). A paradox between religious conviction and recognizing the freedom of others on measuring religious (in)tolerance index in East Java, Indonesia. Cogent Social Sciences, 9(1). https://doi.org/10.1080/23311886.2023.2191443 Hambali, R. Y. A. (2023). The dilemma of religious tolerance: Levinasian critique and proposal. International Journal of Nusantara Islam, 11(2), 300–312. https://doi.org/10.15575/ijni.v11i2.31226 Islam, M. H. (2020). Tolerance limitation in facing religious diversity based on the teaching of Islam. Nazhruna: Jurnal Pendidikan Islam, 3(1), 1–13. https://doi.org/10.31538/nzh.v3i1.483 Mala, A., Zulkarnain, Z., Abu Bakar, M. Y., & Marpuah, S. (2024). Fostering tolerance through inclusive Islamic education: The role of pesantren in navigating global challenges. Jurnal Pendidikan Agama Islam, 12(2), 153–178. https://doi.org/10.15642/jpai.2024.12.2.153-178 Miles, M. B., Huberman, A. M., & Saldaña, J. (2014). Qualitative data analysis: A methods sourcebook (3rd ed.). SAGE Publications. Muhtifah, L., Hudi Prasojo, Z., Sappe, S., & Elmansyah, E. (2021). The theology of Islamic moderation education in Singkawang, Indonesia: The city of tolerance. HTS Teologiese Studies / Theological Studies, 77(4). https://doi.org/10.4102/hts.v77i4.6552 Muis, A. (2026). Incorporating religious moderation values into the Islamic religious education curriculum in secondary education: A systematic review of goals, experiences, methods, and evaluation. British Journal of Religious Education, 48(2), 248–262. https://doi.org/10.1080/01416200.2025.2598619 Mulyana, R. (2023). Religious moderation in Islamic religious education textbook and implementation in Indonesia. HTS Teologiese Studies / Theological Studies, 79(1). https://doi.org/10.4102/hts.v79i1.8592 Muslih, Muslam, Darmi, R., Ramlan, S. R., Abdullah, R. R., & Luthfan, M. A. (2024). Religious moderation in primary education: Experiences of teachers in Indonesia and Malaysia. Jurnal Pendidikan Agama Islam, 21(2), 477–491. https://doi.org/10.14421/jpai.v21i2.10009 Nasir, M., & Rijal, M. K. (2021). Keeping the middle path: Mainstreaming religious moderation through Islamic higher education institutions in Indonesia. Indonesian Journal of Islam and Muslim Societies, 11(2), 213–241. https://doi.org/10.18326/ijims.v11i2.213-241 Rahmat, M., & Yahya, M. W. B. H. M. (2022). The impact of inclusive Islamic education teaching materials model on religious tolerance of Indonesian students. International Journal of Instruction, 15(1), 347–364. https://doi.org/10.29333/iji.2022.15120a Saada, N. (2023). Educating for global citizenship in religious education: Islamic perspective. International Journal of Educational Development, 103, 102894. https://doi.org/10.1016/j.ijedudev.2023.102894 Sahin, A. (2018). Critical issues in Islamic education studies: Rethinking Islamic and Western liberal secular values of education. Religions, 9(11), 335. https://doi.org/10.3390/rel9110335 Sakallı, Ö., Tlili, A., Altinay, F., Karaatmaca, C., Altinay, Z., & Dağli, G. (2021). The role of tolerance education in diversity management: A cultural historical activity theory perspective. SAGE Open, 11(4). https://doi.org/10.1177/21582440211060831 Sirry, M., Suyanto, B., Sugihartati, R., Kartono, D. T., & Yani, M. T. (2024). Teachers’ perspectives on tolerance education in Indonesian high schools. British Journal of Religious Education, 46(4), 505–519. https://doi.org/10.1080/01416200.2024.2345213 Sodiqin, A., & Umroh, R. R. (2024). Towards an interreligious fiqh: A study of the culture-based religious tolerance in the Kaloran community, Central Java, Indonesia. Al-Jami’ah: Journal of Islamic Studies, 61(1), 159–180. https://doi.org/10.14421/ajis.2023.611.159-180 Subchi, I., Zulkifli, Z., Latifa, R., & Sa’diyah, S. (2022). Religious moderation in Indonesian Muslims. Religions, 13(5), 451. https://doi.org/10.3390/rel13050451 Suyanto, B., Sirry, M., Sugihartati, R., Kartono, D. T., & Yani, M. T. (2024). Problems of religious literacy in Indonesian education. Journal of Religious Education, 72(2), 165–181. https://doi.org/10.1007/s40839-024-00228-1 Verkuyten, M., Adelman, L., & Yogeeswaran, K. (2022). Tolerance as forbearance: Overcoming intuitive versus deliberative objections to cultural, religious, and ideological differences. Psychological Review, 129(2), 368–387. https://doi.org/10.1037/rev0000228 Verkuyten, M., Yogeeswaran, K., & Adelman, L. (2023). The social psychology of intergroup tolerance and intolerance. European Review of Social Psychology, 34(1), 1–43. https://doi.org/10.1080/10463283.2022.2091326 Wahyono, S. B., Budiningsih, A., Suyantiningsih, S., & Rahmadonna, S. (2022). Multicultural education and religious tolerance: Elementary school teachers’ understanding of multicultural education in Yogyakarta. Al-Jami’ah: Journal of Islamic Studies, 60(2), 467–508. https://doi.org/10.14421/ajis.2022.602.467-508 Yazdani, A. (2020). La cultura de la paz y la tolerancia religiosa desde una perspectiva islámica. Veritas, 47, 151–168. https://doi.org/10.4067/S0718-92732020000300151